2022
DOI: 10.1002/solr.202200243
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Carbon‐Nanotube‐Based Materials for Photocatalytic Applications: A Review

Abstract: As one of the most outstanding allotropes of carbon assembled with a cylindrical nanostructure, carbon nanotubes (CNTs) have attracted extensive attention in the areas of material science and engineering due to their unique structural characteristics and physicochemical properties. Very recently, versatile hierarchical CNT‐based photocatalysts are of considerable interest in current research and applications ranging from fuel generation to environmental purification. Therefore, it is necessary to summarize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 214 publications
0
8
0
Order By: Relevance
“…Owing to their large surface areas, intriguing electronic properties, unique physicochemical properties, and high aspect ratios, CNTs and CNFs are promising candidates for the design and synthesis of novel photocatalysts. In general in CNT-based photocatalyst systems, CNTs act as “electron sinks” that receive photogenerated electrons from the semiconductor, thereby realizing the effective separation of photogenerated electron-hole pairs [ 84 ]. They also facilitate electron transport in heterogeneous photocatalyst systems through “electron bridges.” It is worth mentioning that some researchers observed that the absorption edge of CNT-based photocatalysts shifts to a higher wavelength than that of bare photocatalysts.…”
Section: Carbon-based Photocatalystsmentioning
confidence: 99%
“…Owing to their large surface areas, intriguing electronic properties, unique physicochemical properties, and high aspect ratios, CNTs and CNFs are promising candidates for the design and synthesis of novel photocatalysts. In general in CNT-based photocatalyst systems, CNTs act as “electron sinks” that receive photogenerated electrons from the semiconductor, thereby realizing the effective separation of photogenerated electron-hole pairs [ 84 ]. They also facilitate electron transport in heterogeneous photocatalyst systems through “electron bridges.” It is worth mentioning that some researchers observed that the absorption edge of CNT-based photocatalysts shifts to a higher wavelength than that of bare photocatalysts.…”
Section: Carbon-based Photocatalystsmentioning
confidence: 99%
“…One prominent emerging application is the use of CNTs and nanotube heterostructures in photocatalysis, where filled or functionalized nanotubes can boost the rate of photocatalytic redox reactions that remove pollutants, perform CO 2 reduction, or produce hydrogen from water. 14 16 For such applications, knowledge of the electronic and optical properties of the nanocomposite is vital, in particular because it has reported that the infiltrated material can significantly modify the electronic nature of the outer nanotubes. 17 20 For example, filling with Te can enhance the charge-carrying capacity of boron nitride nanotubes, 12 growing copper halide nanocrystals inside CNTs can lead to the creation of new carbon-copper energy levels, 21 and filling with alkane can significantly enhance the tunability of the optical performance of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first reports of filling carbon nanotubes (CNTs) with guest materials 3 decades ago, there has been huge interest in the creation of extremely thin one-dimensional (1D) hybrid materials such as CNTs filled with molecules, other nanotubes, nanowires (NWs) or nanoclusters. One prominent emerging application is the use of CNTs and nanotube heterostructures in photocatalysis, where filled or functionalized nanotubes can boost the rate of photocatalytic redox reactions that remove pollutants, perform CO 2 reduction, or produce hydrogen from water. For such applications, knowledge of the electronic and optical properties of the nanocomposite is vital, in particular because it has reported that the infiltrated material can significantly modify the electronic nature of the outer nanotubes. For example, filling with Te can enhance the charge-carrying capacity of boron nitride nanotubes, growing copper halide nanocrystals inside CNTs can lead to the creation of new carbon-copper energy levels, and filling with alkane can significantly enhance the tunability of the optical performance of CNTs . Further, hybrid nanotube materials,including heterostructures with BN and MoS 2 and other nanotubes, exhibit unique properties such as unconventional Raman signatures, distinct phase transitions, and interesting charge-transfer processes between their constituents. ,, Tremendous developments in liquid-phase separation techniques have enabled the purification of not only the “host” material, such as single-walled carbon nanotubes (SWCNTs), but also nanotube heterostructures based on their metallicity or electronic properties. , Nanotube heterostructures are also attractive components for nanoelectronics, where they can act as functional thermoelectric, photovoltaic, or conductive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic semiconducting nanostructured materials have been extensively studied for decades as heterogeneous photocatalysts for solar energy harvesting. Among these, carbon-based materials, metal–organic frameworks, metal oxides, , chalcogenides, chalcopyrites, kesterites, perovskites, and oxyhalides remained in the forefront. Developments of such new materials, along with studies of their crystal structures and optical bandgaps, are also continuing, in order to meet the current challenges of harvesting energy while providing environmental remedies.…”
Section: Introductionmentioning
confidence: 99%